Improvement of mechanical properties and low-temperature fracture characteristics of pipe steel; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Derevyagina L. S. Lyudmila (2018, 2018)
Title screen